Vimentin modulates focal adhesion dynamics in directionally migrating fibroblasts - Modi, Mayank (My University, 2018)
Cell migration is an integral process in several physiological events essential for normal functioning of an organism. Cell migration is a mechanistic phenomenon that occurs in many steps including cell polarization, attachment to the substratum, extension of leading edge, cell body movement, and detachment of the cell rear. This process is mediated by the interaction of cytoskeletal proteins such as actin and microtubules with focal adhesion at the substratum and other signalling factors. Fibroblastic migration plays a significant role in macrophage mediated immune response, wound healing and metastasis, however the role of cytoskeletal protein vimentin is still poorly understood. It has been demonstrated that vimentin knockout fibroblasts show decreased wound healing and delayed migration. Here we are studying the effects of vimentin on the dynamics of focal adhesion proteins in fibroblasts in an in vitro wound healing assay. We demonstrate that vimentin influences the morphology, turnover, and behavioural dynamics of focal adhesions in directionally migrating fibroblasts. The data demonstrates that the disassembly rate of focal adhesions in vimentin knockout cells is significantly higher than their wild type counterpart. In addition, vimentin null cells form lower number of focal adhesions with smaller size, express lesser amount of focal adhesions proteins like paxillin, focal adhesion kinase, and vinculin. Vimentin filament disruption has been shown to dramatically affect the morphology of focal adhesions. There is a marked variation in the overall behaviour of focal adhesions in migrating cells in terms of size and shape over time in vimentin null mouse embryonic fibroblasts (MEFs). MEF vimentin null cells appear to have disorganized and disoriented adhesions in the direction of migration. These cumulative findings indicate the significance of vimentin intermediate filament in modulating focal adhesions during fibroblastic migration and help understand the interplay in a biologically relevant context.
Keywords: Vimentin, intermediate filaments, cell migration, focal adhesions